Technical and economic analysis of solvent-based lithium-ion electrode drying with water and NMP. Issue 2 (25th January 2018) - Wood, David L.; Quass, Jeffrey D.; Li, Jianlin; Ahmed, Shabbir; Ventola, David; Daniel, Claus
ABSTRACT: Processing lithium-ion battery (LIB) electrode dispersions with water as the solvent during primary drying offers many advantages over N -methylpyrrolidone (NMP). An in-depth analysis of the comparative drying costs of LIB electrodes is discussed for both NMP- and water-based dispersion processing in terms of battery pack $/kWh. Electrode coating manufacturing and capital equipment cost savings are compared for water vs. conventional NMP organic solvent processing. A major finding of this work is that the total electrode manufacturing costs, whether water- or NMP-based, contribute about 8–9% of the total pack cost. However, it was found that up to a 2 × reduction in electrode processing (drying and solvent recovery) cost can be expected along with a $3–6 M savings in associated plant capital equipment (for a plant producing 100, 000 10-kWh Plug-in Hybrid Electric Vehicle (PHEV) batteries) using water as the electrode solvent. This paper shows a different perspective in that the most important benefits of aqueous electrode processing actually revolve around capital equipment savings and environmental stewardship and not processing cost savings.